Visualisasi Data Kependudukan Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Musi Banyuasin - Rica Damayanti Putri; Alex Wijaya (APTIKOM SUMSEL, 2020)
Population data from the Department of Population and Civil Registration can be used by other agencies according to the needs of that agency. The Department of Population and Civil Registration uses SIAK (Sistem Informasi Administrasi Kependudukan /Population Administration Information System) for its service processes, the SIAK application is an application made by the Director General of Department of Population and Civil Registration of the Ministry of Home Affairs. The SIAK application still has limited features for operators in the District, for this reason the SIDAK application was created for the utilization of population data in Musi Banyuasin Regency. In this SIDAK application, there is no feature available for visualizing graphical data so that the desired data can be easily analyzed in aggregate data. For the data visualization, the authors took the data from the SIAK database conversion to the SIDAK application. The data taken is the aggregate data on the number of populations, mandatory ID card, birth, death, move, arrival, occupation, religion, education, blood group, marital status, persons with disabilities, age groups. Therefore, we need a tool that capable of visualizing population data using a website in the form of a dashboard system at the Department of Population and Civil Registration. This population data visualization system development uses the Extreme Programming method